Alexithymia and the Reduced Ability to Represent the Value of Aversively Motivated Actions - Starita, Francesca; di Pellegrino, Giuseppe (Frontiers in Psychology, 2018)
Alexithymia is a subclinical trait defined by difficulties in identifying and describing feelings and a cognitive style avoidant of introspection. Extensive literature shows that alexithymia is characterized by multifaceted impairments in processing emotional stimuli. Nevertheless, the mechanisms that may account for such impairments remain elusive. Here, we hypothesize that alexithymia may be understood as impairment in learning the emotional value of one’s own actions and test this comparing performance of participants with high (HA) and low (LA) levels of alexithymia on a probabilistic selection task. Results show that, compared to LA, HA need more time to learn the value of individual stimuli and associated actions as difference in reinforcement rate between stimuli decreases. In addition, HA appear less able to generalize the value of previously learned actions that lead to a negative outcome, to make adaptive choices in a new context, requiring more time to avoid the most negative stimulus between two negative stimuli. Together, the results indicate that individuals with alexithymia show impaired learning of the value of aversively motivated actions. We argue that this impairment may hinder the construction of internal representations of emotional stimuli and actions and represent a mechanism that may account for the difficulties of alexithymia in processing emotional stimuli.